GOOD GOVERNANCE SEBAGAI UPAYA MENINGKATKAN KUALITAS DEMOKRASI LOKAL DI KABUPATEN ASAHAN - Pinem, Windawati; Prayetno; Ramadhan, Taufiq; Syahputra, Hikmawan (FISIP Universitas Malikussaleh, 2025)
This study aims to analyze the application of good governance principles as an effort to improve the quality of local democracy in Asahan Regency in 2024. The reform and implementation of regional autonomy has changed the relationship between provincial and district/city governments to no longer be hierarchical. This change gave rise to strong regional egocentrism and had an impact on the deviation of the meaning of democracy. Local democracy is often used as a means of justifying anarchist practices in the name of freedom. In fact, the achievement of good governance requires quality democracy, characterized by freedom, equality, and strong institutional capacity. This study uses a descriptive qualitative approach with data collection techniques through Focus Group Discussion (FGD) and data analysis using triangulation. The state of the art research focuses on three main indicators: civil liberties, political equality, and the capacity of democratic institutions. The results of the study show that Asahan Regency has implemented the principles of good governance well. This is reflected in the improvement of the quality of local democracy, broad public participation, government accountability, and the strengthening of democratic institutions at the district level. These findings underscore the importance of integration between good governance and local democratic development.